A Comparative Phase I Study of Combination, Homologous Subtype-C DNA, MVA, and Env gp140 Protein/Adjuvant HIV Vaccines in Two Immunization Regimes - Joseph, Sarah; Quinn, Killian; Greenwood, Aldona; Cope, Alethea V.; McKay, Paul F.; Hayes, Peter J.; Kopycinski, Jakub T.; Gilmour, Jill; Miller, Aleisha N.; Geldmacher, Christof; Nadai, Yuka; Ahmed, Mohamed I. M.; et al. (Frontiers in Immunology, 2017)
There remains an urgent need for a prophylactic HIV vaccine. We compared combined MVA and adjuvanted gp140 to sequential MVA/gp140 after DNA priming. We expected Env-specific CD4+ T-cells after DNA and MVA priming, and Env-binding antibodies in 100% individuals after boosting with gp140 and that combined vaccines would not compromise safety and might augment immunogenicity. Forty volunteers were primed three times with DNA plasmids encoding (CN54) env and (ZM96) gag-pol-nef at 0, 4 and 8 weeks then boosted with MVA-C (CN54 env and gag-pol-nef) and GLA-AF adjuvanted CN54gp140. They were randomised to receive them in combination at the same visit at 16 and 20 weeks (accelerated) or sequentially with MVA-C at 16, 20, and GLA-AF/gp140 at 24 and 28 weeks (standard). All vaccinations were intramuscular (IM). Primary outcomes included >= grade 3 safety events and the titre of CN54gp140-specific binding IgG. Other outcomes included neutralisation, binding antibody specificity and T-cell responses. Two participants experienced asymptomatic =>grade 3 transaminitis leading to discontinuation of vaccinations, and three had grade 3 solicited local or systemic reactions. 100% made anti-CN54gp140 IgG and combining vaccines did not significantly alter the response; geometric mean titre 6424 (accelerated) and 6578 (standard); neutralisation of MW965.2 Tier 1 pseudovirus was superior in the standard group (82% versus 45% responders, p= 0.04). T-cell ELISPOT responses were CD4+ and Env-dominant; 85% and 82% responding in the accelerated and standard groups respectively. Vaccine-induced IgG responses targetted mulitiple regions within gp120 with the V3 region most immunodominant and no differences between groups detected. Combining MVA and gp140 vaccines did not result in increased adverse events and did not significantly impact upon the the titre of of Env-specific binding antibodies which were seen in 100% individuals. The approach did however affect other immune responses; neutralising antibody responses, seen only to Tier 1 pseudoviruses, were poorer when the vaccines were combined and whilst T-cell responses were seen in >80% individuals in both groups and similarly CD4 and Env dominant, their breadth/polyfunctionality tended to be lower when the vaccines were combined, suggesting attenuation of immunogenicity and cautioning against this accelerated regimen. EUDRACT TC 2012-003277-26 / NCT01922284